GAMBARAN PERSEPSI MASYARAKAT TERHADAP TERAPI KOMPLEMENTER DI KLINIK LATU USADHA BALI - I Putu Eka Viqtrayana; Gede Agung Ratnata; I Made Dwi Krisma Prataba (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2022)
Background: Complementary and alternative medicine has developed globally, with these developments there are several things that make it possible to increase the use of complementary and alternative medicine, one of which is public perception. Broad public perception will also affect the public's desire to use complementary and alternative medicine as the therapy of choice for health. The purpose of this study was to determine the public's perception of complementary and alternative medicine at the Latu Usadha Clinic in Bali. Methods: This research is a quantitative descriptive study. The research was conducted at Latu Usadha Clinic, Bali. Data obtained by using purposive sampling with a total of 37 respondents. The instrument in this study used a questionnaire. The data analysis technique used univariate analysis. Results: Based on the results of the study, it showed that of the 37 respondents, most of the people who gave positive perceptions of complementary and alternative therapies were 33 people with a percentage of 89.2%. The positive perception of the community towards cupping therapy was 27 people (73%). Positive perceptions of acupuncture and acupressure therapy were 36 people (97.3%). Positive perception of reflexology as many as 32 people (86.5 %). Positive perceptions of herbal medicines were 32 people (86.5%). Positive perceptions about the advantages and disadvantages of complementary and alternative medicine are 27 people (73%). There were 10 people (27%), positive perceptions about fracture specialists and 27 people (73%). There were 37 people (100%) negative perceptions about the dukun spraying. Conclusion: Most gave a positive perception (89.2%) of complementary and alternative therapies. The public is expected to know the effectiveness of complementary and alternative medicine, and can choose complementary and alternative treatments that have clear and correct standard procedures.